“Nature of mort” vs “still life” in a poem “Naturmort” of Igor Kalynets: between a lyric poetry and painting - Savchuk, Hryhorii (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2025)
In modern literary criticism a problem of study of work of Ukrainian sixties, in particular intermedial components is actual. Papers of scientists testify that Ihor Kalynets’s lyric poetry offers a rich material for a researcher.The aim of the paper is illumination of literary-picturesque correlations in a verse “Naturmort”. The intermediate-comparative analysis is used. Composition of picture of the Ukrainian artist that chose the middle scale of image is analysed, it allows to draw detail elements. First strophe of verse “Naturmort” passes syncretism nature of picture, that contains the elements of interior, landscape and actually of still life. “Congestion” of “heroes” of this linen is felt, but a picture is not overloaded semiotic. Every element is called to establishment of equilibrium and harmony. The same intension is translated by the I. Kalynets’s verse: at the beginning of work an epithet “comfortable” is repeated three times.The techniques of “picture within a picture” and “refrain without refrain” are analyzed.The further development of the lyrical plot leads to the opposition “nature mort” vs “still life” (“dead nature” vs “still life”). This antonymic pair can be read through the prism of the dichotomy of “eros and thanatos” (love, happiness and death, destruction). I. Kalynets chooses eros and rejects thanatos, which speaks volumes about the worldview dominants in his life, about the remarkable willpower of a prisoner of conscience, the ability to see and honor life in all its manifestations.It is concluded that the poem contains formal and genre features of the riturnel and triolet.Reflections on I. Kalynets's philosophical and intermedial intentions in the poem “Naturemort” are summarized by the idea that for the poet, the feeling of harmony in the soul, love for life, which naturally develops into a desire to harmonize the environment, are organically true. The “still life” prevails over the “dead nature”.